PENGARUH KONSENTRASI PEREKAT TEPUNG TAPIOKA DAN TANAH LIAT TERHADAP MUTU BRIKET BATU BARA - Tamrin - (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2016)
Making coal briquettes require tapioca glue and clay. The purpose of this research is studying the effect ofconcentration tapioca glue and clay to characteristic coal briquette. Research carried out by treatment with aconcentration of starch, clay and coal flour respectively as follows; a) 2%, 18%, 80%, b) 4%, 14%, 82%, c) 6%,10%, 84% and d) 8%, 6%, 86%. The results are showed that the density of coal briquettes are not affected by theconcentration of glue material, but it is influenced by the pressure of the tool at the time of manufacture. The lowerthe content of clay in the briquettes, the stronger the briquettes were produced and the lower the number ofbriquettes were broken when dropped at a height of 2 m. The higher the clay content of the briquettes, so the timefor the initial combustion, the temperature of the plate surface reached 180 °C and the duration of briquettebecame ashes are longer. The rate of combustion of coal briquettes are made lower than the rate of briquettescombustion from briquettes non carbonization and carbonizationKey word : coal briquette, tapioca, clay, start up combustion dan carbonisation